2021
DOI: 10.3390/molecules26020255
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity and Mechanism of Isookanin, Isolated by Bioassay-Guided Fractionation from Bidens pilosa L.

Abstract: Bidens pilosa L. (Asteraceae) has been used historically in traditional Asian medicine and is known to have a variety of biological effects. However, the specific active compounds responsible for the individual pharmacological effects of Bidens pilosa L. (B. pilosa) extract have not yet been made clear. This study aimed to investigate the anti-inflammatory phytochemicals obtained from B. pilosa. We isolated a flavonoids-type phytochemical, isookanin, from B. pilosa through bioassay-guided fractionation based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…All these elements stimulate the development of inflammation and worsen the inflammation over the harmonious interaction with further inflammatory intermediaries and there are reports that in variety of inflammatory ailments including asthma and colitis the expression levels of PGE2 and NO is elevated [15–17]. Our study revealed that Viphyllin efficiently inhibited the secretion of PGE2 and NO, and proinflammatory cytokines in LPS-challenged macrophages at safer dose, our findings are consistent with earlier published studies [18, 19]. COX-2.…”
Section: Discussionsupporting
confidence: 93%
“…All these elements stimulate the development of inflammation and worsen the inflammation over the harmonious interaction with further inflammatory intermediaries and there are reports that in variety of inflammatory ailments including asthma and colitis the expression levels of PGE2 and NO is elevated [15–17]. Our study revealed that Viphyllin efficiently inhibited the secretion of PGE2 and NO, and proinflammatory cytokines in LPS-challenged macrophages at safer dose, our findings are consistent with earlier published studies [18, 19]. COX-2.…”
Section: Discussionsupporting
confidence: 93%
“…The tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) can significantly promote the progression of inflammation. [26] Thus, the levels of TNF-α and IL-6 in the LPS-stimulated RAW 264.7 cell were determined by ELISA. As showed in Figure 7, when the RAW 264.7 cells were pretreated with compound 11, the levels of TNF-α, and IL-6 induced by LPS were dose-dependently downregulated.…”
Section: Resultsmentioning
confidence: 99%
“…Many natural compounds—for example, resveratrol, curcumin, or quercetin—can target a wide variety of molecules, implying that natural products might be effective inhibitors [ 42 ]. Isookanin is a phenolic flavonoid component contained in some plants, such as Asteraceae [ 26 ] and Leguminosae [ 28 ], and its anti-inflammatory efficacy and mechanism of action have already been revealed in our previous research [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Isookanin (C 15 H 12 O 6 , molecular weight: 288.3) is a phenolic flavonoid presented in Bidens extract [ 26 ]. It has been reported that isookanin possesses some biological properties, including antioxidative [ 27 , 28 ] and anti-diabetic properties [ 27 ], anti-inflammatory effects [ 29 ] and an ability to inhibit α-amylase [ 26 ]. However, the antiangiogenic effects and mechanism thereof have not been studied yet.…”
Section: Introductionmentioning
confidence: 99%